Prospective radiotherapy quality Assurance leads to delineation guideline refinements for recurrent rectal cancer: Experience from the PelvEx II study - F. Piqeur; B.J.P. Hupkens; D.M.J. Creemers; S. Nordkamp; M. Berbee; J. Buijsen; H.J.T. Rutten; C.A.M. Marijnen; J.W.A. Burger; H.M.U. Peulen (Clinical and Translational Radiation Oncology)
Introduction: Target volume delineation in locally recurrent rectal cancer (LRRC) is clinically challenging. To ensure the quality of chemoradiotherapy (CRT) within the PelvEx II trial, a delineation guideline was developed and prospective quality assurance (QA) was instated for all patients. Guideline adherence, the impact of QA on target volumes, and subsequent guideline refinements are described in this paper. Methods and materials: All PelvEx II patients, either RT naive patients (50–50.4 Gy) or reirradiation (30 Gy) patients, were eligible for QA prior to CRT. An online meeting with the treating physician and the QA team was planned for each patient prior to treatment, to peer review delineations. Adherence to each of the 7 (reirradiation) or 8 (RT naive) guideline recommendations was scored. Suggested target volume adjustments and any reasons to deviate from protocol were noted. When applicable, target volumes before and after QA were compared. Possible protocol refinements were discussed amongst the trial QA team. Results: Prospective review of 113 cases of LRRC was performed, resulting in a high QA compliance rate of 90 %. All guideline recommendations were followed in 53 % of cases. Changes to the GTV and CTV were advised in 21 and 39 cases respectively. A median increase of GTV (+29 % (p < 0.001)) and CTV (+15 % (p < 0.001)) was seen in reirradiation patients, versus a median CTV increase of + 6 % (p = 0.002) in RT naive patients following QA. Deviations from protocol were accepted in 30 cases (27 %). Thirteen protocol refinements were agreed upon. Conclusion: Peer-review of LRRC target volumes leads to altered target volumes in up to 48% of cases, resulting in an updated delineation guideline.